The Contributions of Green Concrete Towards Sustainable Built Environment - Loh, Ja Hin (2021)
Environmental issue has become global concern as it is getting serious and worse which eventually brings unforeseeable destructive impacts. Among the industries, construction industry is regarded as one of the main contributor to this issue. In this context, sustainability in construction with the goal to reduce industry’s impacts on the environment is becoming widely adopted. To tackle the issue from the fundamental aspect, green concrete is introduced to the industry. Concrete is known as one of the most widely used material on the Earth, which on the other hand, poses significant environmental issue. About 8 – 10% of carbon dioxide emissions are generated by the cement industry. In addition, greenhouse gases are released to the environment when natural aggregates are crushed and heated at the elevated temperatures, which directly intensifies environmental burdens. Therefore, this research is aimed to investigate the impacts of green concrete towards the sustainable built environment. The numerous benefits of green concrete are determined in the study. Furthermore, the application of green concrete in construction projects are identified as green concrete is found still uncommon in many countries. Since the study is more relevant to construction parties, online questionnaire is distributed to contractor company in Selangor area to obtain their perspectives regarding this topic. The primary data collected is presented in bar chart as well as pie chart and is then analysed through frequency table. The research findings show that green concrete is a sustainable and environmental-friendly material. The most significant benefit of green concrete towards environment is to reduce waste as green concrete involves utilisation of waste materials from different industries.